FENOMENA REMAJA PENGGUNA JASA PIJAT PLUS PLUS DI KOTA PANGKAL PINANG PROVINSI BANGKA BELITUNG - Muji Muji Suryanto (Department of Sociology, Faculty of Social and Political Sciences, Sriwijaya University, 2021)
This study aims to determine the teenage phenomenon massage service users plus plus in Pangkal Pinang Bangka Belitung province. The method used in this research is descriptive qualitative method. Data collection techniques in this study using observation, interview and documentation. The number of informants in this study a total of 11 informants. Determination of informants in this study using purposive technique. This study uses the concept of phenomenology of Alfred Schutz. These results indicate that teens plus plus massage service users influenced by the behavior and motives of adolescents themselves. Behavioral factors of adolescent service users pjat plus plus affected in terms of the characteristics of the adolescents themselves which include age, gender and education.